Ten years of Kaesong Industrial Complex: A brief history of the last economic cooperation project of the Korean peninsula - Ralph M. Wrobel (Economic and Environmental Studies (E&ES), 2014)
After fife month the special economic zone Kaesong Industrial Complex (KIC) in North Korea was reopened again on 16 September 2013. By this way, it is the last remaining centrepiece of North-South economic cooperation on the Korean peninsula. Established during the period of "Sunshine policy" (1998 - 2007) and opened in 2003 the project was controversial from the first beginning. This article will give an overview about the history of the project explaining its economic importance for both sides and the peaceful development in Korea. While KIC was assumed to strengthen inter-Korean relations, to improve knowledge of North Koreans about market economy, competition and democracy at all, it failed. What remains is a possibility for North Korea to earn money from the South - and for South Korea a possibility to use the cheap labour force of the North. In contrast, all political attempts grasped at nothing. Therefore, also the last remaining relict of this era should be closed down finally.
Keywords: 330; Special Economic Zones; economic and political cooperation; North Korea; South Korea